Perspectives on Life Cycle Assessment Application and Research in Thailand - Shabbir Gheewala; Thumrongrut Mungcharoen (Indonesian Journal of Life Cycle Assessment and Sustainability, 2017)
Life Cycle Assessment (LCA) has been initiated in Thailand since the late 1990s with the first life cycle inventory (LCI) of the electricity grid mix and the offering of the first full graduate course. Since then it has come a long way through the development of the national LCI database and application in various research, industry as well as policy initiatives. LCA has been used extensively as an evaluation and decision tool in agri-food products, energy as well as many other sectors. Many graduate studies as well as research and industrial LCA projects have been performed. Related activities include the proliferation of carbon footprint labeling and application in green purchasing initiatives. Industry has been very actively participating in the carbon footprinting applications, some of them extending their interest to full LCAs for environmental performance evaluation and sustainability reporting. More recently, efforts have also been moving in the direction of looking at life cycle impact assessment methods from a Thailand perspective. Also, with interest in LCA from the policy making perspective, a capacity building effort has been initiated to train researchers in conducting LCA-related research on a sustained basis and ensure that Thailand keeps abreast of the international trends and discussions.